Analisis Kandungan Protein dan Mutu Organoleptik Cookies Subtitusi Tepung Ikan Teri dan Kacang Tunggak sebagai Makanan Selingan pada Balita - Nur Ayni; Tri Yunita Fitria Damayanti; Dian Ayu Ainun Nafies (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
Stunting is one of the nutritional problems in Indonesia caused by failure to thrive which is influenced by chronic malnutrition. One of the factors causing stunting is an imbalance in protein intake. To meet the protein needs of toddlers, cookies are made, substitution cookies, anchovy meal and cowpea flour can be used as an alternative snack for toddlers. The purpose of this study is to determine the effect of substitution of anchovy meal and cowpea meal on the protein value and organoleptic quality of cookies This study used True Experimental with Complete Randomized Design (RAL), 4 levels of treatment and 6 times replication. The treatment applied is by a ratio of wheat flour: anchovy meal: cowpea flour at each P0 (100:0:0), P1 (70:20:10), P2 (60:10:30), P3 (50:30:20) The results showed that there was an effect of increasing protein levels in cookies with the substitution of anchovy meal and cowpea flour which showed the highest value in P3 treatment. There was a significant effect on organoleptic quality shown by the Kruskall-Wallis test (p<0.005) and continued mann-whitney follow-up tests showed differences in all treatments. The conclusion of this study is that cookies substitution of anchovy meal and cowpea flour have an influence on protein levels, and organoleptic quality.